The effect of problem-based learning assisted with concept mapping founded on cognitive style on the creativity of writing exposition text - Rubiah, Rubiah; Degeng, I Nyoman Sudana; Setyosari, Punadji; Kuswandi, Dedi (Creativity studies, 2024)
The aim of this research is to obtain another point of view with collaborative problem-based learning to increase writing creativity in the field of scientific work in the form of exposition text by investigating cognitive style as an individual character and using concept mapping media. This study uses descriptive research methods and multivariate analysis is used to provide a clear picture of writing creativity that considers the use of learning methods, concept mapping media, and students’ cognitive style backgrounds. The research subjects were students of the second-semester Islamic religious education study program from the Islamic Senior High School Diniyah Putri Pekanbaru, Indonesia. Sample selection was done by means of cluster random sampling. The sample was divided into two, the experimental class which collected 30 people, and the control class with a number of 30. The cognitive style must be considered in the application of the learning method. Students with field-dependent cognitive styles are more adaptable in collaborative learning. The use of media mapping to foster writing creativity was evident during the research. Concept mapping, which involves higher-order thinking skills, stimulates students to continue to involve the imagination in their creative process. Several educational implications are discussed and can be used as future research directions. The interpretation results are obtained by considering the relevant literature findings.